Design And Development Of Automated Engine Test Cell System For Single Cylinder Diesel Engine - Lee, Hong Lean (Universiti Sains Malaysia, 2017)
Engine is getting more advanced which provided higher energy conversion as compared to when it first invented. Besides, the development of alternative fuels such as biodiesel caused more and more research and studies in the performance of engine. Due to large amount of data that must be collected in conventional engines, engineers are looking toward new methods of accelerating aside from manually setting the parameters. One of the solution is to make it automated and designing the software for engine test cell system by using processing device and measuring sensor with a reduced cost without compromising the performance and capabilities of an engine test cell. Automating engine test can greatly reduce the amount of testing time as well as provide robustness that manually changing setpoints cannot offer. In this research, in order to investigate the performance, emission and combustion of the engine effectively, an automated test cell has been developed. It provided automated recording of the quantifiable data including the torque measurement, speed measurement, fuel flow measurement, combustion data acquisition and emission data acquisition. It is also designed to provide real-time control on the dynamometer which make us easier to control the engine. A study of performance, emission and combustion characteristic of Palm Methyl Ester biodiesel and diesel, the B100 generally shows lower torque. Power and brake thermal efficiency. However, it have a higher specific fuel consumption. The difference in emission and combustion for B100 are lower CO and CO2 emission by 17-45% and 25-43% and also maximum 52% lower NOx emission.